TELEVISI KAMPUS : Siasat Evolusi Kebudayaan Menjawab Perkembangan Zaman - Suryanto, Hari (Seni Media Rekam ISI Surakarta, 2017)
The campus television is a strategic forum for education and mutual relationships within the six institutes of the arts in Indonesia organised under the BKS-PTSI (Badan Koordinasi Seni PerguruanTinggi Seni Indonesia).The purpose of the forum is to support the education of art and culture and also to promote values of the local wisdom using the streaming tv portal platform for the campus community and the general public. This strategy is to response the development of media and communication technology in Indonesia.Keywords : Campus television,forum,education,art and culture